The rights of persons with disabilities (PWD): the Malaysian legal framework and shariah perspectives - Md Tah, Ikmal Hisham; Mokhtar, Khairil Azmin (2015)
It is unfortunate that disabled persons have been neglected. Although they require proper care and attention they should not be treated differently. They should be given similar opportunity to be developed and progressed as any other human being. The existence of the United Nations (UN) Convention on the Rights of Persons with Disabilities and Optional Protocol (CRPD) has significantly providing the potential of disabled people to claim their rights and creating awareness of their existence both globally and locally. Malaysia has shown it commitment by ratifying the CRPD.Subsequently the Persons with Disabilities (PWD) Act 2008 has been enacted with the intention to protect and promote the rights of this minority group. The Act has been welcomed by the PWD community as there is no proper and comprehensive law directly govern disabled people previously. It provides institutional framework and legal rights to promote and protect PWD. This paper, through conceptual and doctrinal analysis, will explore Malaysian laws governing PWD. In addition, the Islamic law (Shariah) perspectives including terminology, Al-Quran, Hadith and scholars opinions will be discussed to observe as to how disabled people should be treated by Muslim community. The final analysis show that there is harmonious interpretation between Western and Islamic jurisprudence in dealing with this minority group.